The Subtle Sources of Sampling Bias Hiding in Your Data - Ransbotham, Sam (MIT Sloan Management Review, 2017)
Plummeting data acquisition costs have been a big part of the surge in business analytics. We have much richer samples of data to use for insight. But more data doesn't inherently remove sampling bias; in fact, it may make it worse.